Effect of heat treatment on mechanical properties and dimensional accuracy of 3D-Printed black carbon fiber HTPLA - Md Yasir, Ahmad Shah Hizam; Sukindar, Nor Aiman; Abdul Rahman Putra, Ahmad Afif; Choong, Yang Chuan; Kamaruddin, Shafie; Aziz, Azlan; Aminanda, Yulfian; Sulaiman, Mohd Hafis (Elsevier, 2024)
This present study investigated how heat treatment affects the mechanical properties of 3D-printed black carbon fiber HTPLA by manipulating two parameters: heating temperature and holding time. The mechanical properties of 3D-printed black carbon fiber HTPLA components are crucial for assessing their structural integrity and performance. The shrinkage and dimensional accuracy of the 3D-printed parts were also explored using a vernier caliper. The microstructure of both heat-treated and non-heat-treated HTPLA black carbon fiber 3D-printed parts was examined using scanning electron microscopy. Samples were prepared, printed, heat-treated, and mechanically tested, and their microstructure was observed and recorded. The results showed that heat treatment improved the material's strength, hardness, and crystallinity, leading to better mechanical properties. However, statistical analysis indicates no clear evidence that the two factors, optimum heating temperature and holding time, affect the mechanical properties of heat-treated printed parts. Nonetheless, further study suggests that these factors might be important in optimizing the heat treatment process.